THỬ NGHIỆM VIỆC MỞ RỘNG BÀI TOÁN NGƯỢC XÁC ĐỊNH ĐỘ SÂU ĐÁY BỂ TRẦM TÍCH ĐỂ XÁC ĐỊNH ĐỘ SÂU CỦA MÓNG CÓ CẤU TRÚC DẠNG VÒM - Thanh, Đỗ Đức (Vietnam Journal of Science and Technology, 2012)
ATEMPT THE IMPROVEMENT OF GRAVITY INVERSION OF SEDIMENTARY BASIN DEPTH TO DETERMINE THE DEPTH TO BASEMENT OF DOM STRUCTURES In this paper the improvement of gravity inversion of sedimentary basin depth is presented to determine the depth to basement of dom structures. Based on this method, a computer programme is made a code to atempt in bouth two and three dimensional models. Received results of  the modelling shows  highly exact  and stable of the the methods.